ANALISIS KUALITAS PELAYANAN SISTEM X-RAY PADA PT PELINDO CABANG BENOA - NI KADEK INDY PRISITA; A.A. AYU MIRAH KENCANAWATI; GEDE SANTANU (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to assess the service quality of the X-ray system at Benoa Port and provide recommendations for improving service quality at Benoa Port. The analysis methods used are the Service Quality (Servqual) method to identify gaps between the perceptions and expectations of passengers regarding service quality at Benoa Port and the Importance Performance Analysis (IPA) method to determine service improvement priorities. The sample of this study consisted of 96 cruise passengers in 2024. The result of the research using the servqual method indicate that there are gaps in all dimensions. The highest gap is in the tangible dimension with -0,49 and the lowest gap is in the assurance dimension with a gap of -0,24. Overall the average perception score is 3,80 and the average expectation score is 4,19, resulting in a gap of -0,39 and an average Q score of 0,91 indicating that the service quality provided almost meets the passengers expectations but is not yet perfect. The analysis result using Importance Performance Analysis (IPA) methode show a conformity rate (TKi) between importance and performance of 93,65%, indicating that the quality of the X-ray service system at Benoa Port meets the passengers expectations but still requires improvements. Based on the Cartesian Diagram, there are 5 attributes located in quadrant I, which means that improvements are necessary, consisting of the dimensions of tangibles, responsiveness, and empathy